Optimization of the size and location of the FOVs for CBCT capture of the TMJ - Marc Anton Fuessinger; Maximilian Frederik Russe; Leonard Simon Brandenburg; Marc Christian Metzger; Johannes Schulze; Stefan Schlager; Wiebke Semper-Hogg (BMC Oral Health)
Abstract Background Osseous pathologies of the temporomandibular joint (TMJ) such as degenerative joint disease, trauma, and deformity contribute to orofacial morbidity and are considered a major factor in temporomandibular dysfunction. Cone beam computed tomography (CBCT) is a recommended diagnostic tool in imaging of osseous tissue pathologies. However, CBCT contributes to patient radiation exposure, and limiting the CBCT field of view (FOV) may reduce it. This study aims to investigate the possibility and clinical applicability of optimizing the size and location of the FOVs for CBCT capture of the TMJ. Methods Three-dimensional CBCT data sets in which the bilateral positions and dimensions of the TMJs were analyzed. A total of 201 data sets with 402 condyles were mapped in relation to the CBCT device. By transformation into a common coordinate space using the device’s chin rest as a joint denominator, we were able to determine the optimal size and location for uni- and bilateral capture of the TMJ for both best-case and worst-case scenarios with regard to patient positioning. Results The minimal FOVs for unilateral capture were H 28.2 mm × R 22.9 mm in the best-case scenario assuming optimal patient positioning and H 47.0 mm × R 28.3 mm in the worst-case scenario with rotational deviation along the transversal axis. For bilateral capture, we determined the best-case FOV as H 24.9 mm × R 66.5 mm and the worst-case FOV as H 42.8 mm × R 66.7 mm. Discussion This research yields indication-specific FOVs for both uni- and bilateral imaging of the TMJ. Considering the best clinical practices for CBCT imaging, clinically feasible FOV dimensions in consideration of the technical specifications of common CBCT devices can be suggested. The clinical application of the results may help reducing radiation exposure of patients receiving CBCT imaging of the TMJ. The transferability of the present results to other CBCT devices requires further research. Trial registration The study is registered in the German Trial Register with the number DRKS00026149, 2024/02/21.